PEMBERDAYAAN WARGA KARANG TARUNA KELURAHAN TAMARUNANG MELALUI PENGOLAHAN CABAI DI KABUPATEN GOWA - Triana, Dien; Syamsinar, .; Ishak, Andi Abdul Azis (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
Community empowerment through chili processing is an effort to provide knowledge and motivation to utilize the chili harvest in the environment around the partners. The goals are to provide knowledge to partner about the processing of excessive fresh chili post-harvest around the area and provide business opportunities for the chili powder home industry for partner to improve it welfare. The program partner is Karang Taruna Kelurahan Tamarunang, Somba Opu District, Gowa Regency, South Sulawesi Province. The method used in this program are the training and monitoring method. The steps taken are chili processing, evaluation, packaging, and marketing training. The chilli processing training stage teaches partners about the chili processing by utilizing the available chili processing technology. The evaluation phase is carried out through sensory tests of product appearance. The packaging stage is done by packaging the product in a safe container for sale. The marketing phase is carried out using market and consumer networks. The output of this activity is chilli processed products, namely